Analisis Kedudukan I’rab Kalimah Bahasa Arab pada Kitab Al-Imrithi Menggunakan Algoritma Breadth First Search (BFS) - Risalatul Muawanah; Aulia Faqih Rifa'i (JISKA (Jurnal Informatika Sunan Kalijaga), 2018)
Alquran and hadist are the source of life guidance for muslims, and books of scolars as the proponents. The structure of contents use Arabic language, so studying of Arabic language recommended to all of muslims in islam. Difficutly of understanding structure of Arabic languageis in analyzing Irab. Errors in determining harakat offen occur.This research was conducted tobuild the system in determining Irob position consisting of from, category, Irob and position ofkalimah by implemting Artificial Intelligence especially with Breadth First Search.Refer to theresult of the test that research do with so samples of simple sentence, about 90% this systemis able run well. The result test questionnaire , useful from 35 respondents showed 41.0% ofthem strongly agreed, 44.5% agreed, and 14.3% choosen neutral.                                                                                                     Keywords : Al Imrithi, Breadth First Search, Arabic Language, Irab Analysis